The Acceleration Development of Disadvantaged Regions Policy in Post-Pandemic Covid-19 - Saptono Jenar (International Journal of Business, Economics, and Social Development, 2023)
Based on Presidential Regulation Number 18 of 2020 concerning National Mid-Term Development Plan 2020-2024 junto Presidential Regulation Number 63 of 2020 concerning Stipulation of Disadvantaged Regions 2020-2024, stated that currently, 62 districts have the status as disadvantaged regions. Referring to data from the Central Statistics Agency, it is stated that post-pandemic Covid-19, the poverty rate in the Disadvantaged Regions jumped in 2020 to 26.43% while the National Mid-Term Development Plan 2020-2024 target was 23.4%-24% in 2024. To overcome these problems, it is necessary to have a systematic policy made by the government to achieve the target of the accelerated development of disadvantaged regions in 2020-2024. It is also stated in the National Mid-Term Development Plan 2020-2024 that by the end of 2024, the target of 25 districts may be lifted from their disadvantaged status. By using a normative legal research method as well as a statute and conceptual approach, the authors get the results of the research that until this article was written, factually the government's policy was then poured into Presidential Regulation Number 105/2021 concerning the National Strategy of the Acceleration Development of Disadvantaged Regions 2020-2024 which was the legal form that formed as the government policy to overcome the problems that exist in disadvantaged regions 2020-2024 including post-pandemic covid-19. Besides that, the government uses a collaboration strategy to encourage the implementation of the accelerated development of disadvantaged regions 2020-2024 including post-pandemic Covid-19.